Pengembangan Wisata Edukasi Mangrove melalui Kolaborasi Pemerintah Desa dan Masyarakat di Desa Babakan Kecamatan Pangandaran Kabupaten Pangandaran - Sarah Nur Azhar; Kiki Endah; Erlan Suwarlan (JURNAL ILMIAH NUSANTARA, 2025)
This research is motivated by the lack of optimal collaboration between the Village Government and the community in the development of mangrove educational tourism in Babakan Village, Pangandaran District. The problems found include limited budgets for the procurement of educational infrastructure, low community participation, and lack of innovation from the management. This research aims to find out the extent to which the collaboration is running. The method used is descriptive qualitative, with data collection through literature studies, structured interviews, and observations. The results of the study show that the collaboration that has been established has not been optimal. Barriers include limited time and resources to support intensive communication, information complexity that reduces mutual trust and understanding, and differences in priorities and participation saturation that weaken commitment. Efforts that have been made include simplifying information through visual/digital media, establishing more informal discussion forums, and allocating more adequate resources to support sustainable development. It is necessary to increase the role and synergy between all parties so that the development of mangrove educational tourism can run more effectively and sustainably.